Comparative hazard identification of nano- and micro-sized cerium oxide particles based on 28-day inhalation studies in rats. Issue 6 (September 2014) - Gosens, Ilse; Mathijssen, Liesbeth E.A.M.; Bokkers, Bas G.H.; Muijser, Hans; Cassee, Flemming R.
Abstract There are many uncertainties regarding the hazard of nanosized particles compared to the bulk material of the parent chemical. Here, the authors assess the comparative hazard of two nanoscale (NM-211 and NM-212) and one microscale (NM-213) cerium oxide materials in 28-day inhalation toxicity studies in rats (according to Organisation for Economic Co-operation and Development technical guidelines). All three materials gave rise to a dose-dependent pulmonary inflammation and lung cell damage but without gross pathological changes immediately after exposure. Following NM-211 and NM-212 exposure, epithelial cell injury was observed in the recovery groups. There was no evidence of systemic inflammation or other haematological changes following exposure of any of the three particle types. The comparative hazard was quantified by application of the benchmark concentration approach. The relative toxicity was explored in terms of three exposure metrics. When exposure levels were expressed as mass concentration, nanosized NM-211 was the most potent material, whereas when expression levels were based on surface area concentration, micro-sized NM-213 material induced the greatest extent of pulmonary inflammation/damage. Particles were equipotent based on particle number concentrations. In conclusion, similar pulmonary toxicity profiles including inflammation are observed for all three materials with little quantitative differences. Systemic effects were virtually absent. There is little evidence for a dominant predicting exposure metric for the observed effects.